Neonatal Hemodynamics: From Developmental Physiology to Comprehensive Monitoring - Vrancken, Sabine L.; van Heijst, Arno F.; de Boode, Willem P. (Frontiers in Pediatrics, 2018)
Maintenance of neonatal circulatory homeostasis is a real challenge, due to the complex physiology during postnatal transition and the inherent immaturity of the cardiovascular system and other relevant organs. It is known that abnormal cardiovascular function during the neonatal period is associated with increased risk of severe morbidity and mortality. Understanding the functional and structural characteristics of the neonatal circulation is, therefore, essential, as therapeutic hemodynamic interventions should be based on the assumed underlying (patho)physiology. The clinical assessment of systemic blood flow (SBF) by indirect parameters, such as blood pressure, capillary refill time, heart rate, urine output, and central-peripheral temperature difference is inaccurate. As blood pressure is no surrogate for SBF, information on cardiac output and systemic vascular resistance should be obtained in combination with an evaluation of end organ perfusion. Accurate and reliable hemodynamic monitoring systems are required to detect inadequate tissue perfusion and oxygenation at an early stage before this result in irreversible damage. Also, the hemodynamic response to the initiated treatment should be re-evaluated regularly as changes in cardiovascular function can occur quickly. New insights in the understanding of neonatal cardiovascular physiology are reviewed and several methods for current and future neonatal hemodynamic monitoring are discussed.